Application of network pharmacology in the study of mechanism of Chinese medicine in the treatment of ulcerative colitis: A review - Zheng, Shihao; Xue, Tianyu; Wang, Bin; Guo, Haolin; Liu, Qiquan (Frontiers in Bioinformatics, 2022)
Network pharmacology is a research method based on a multidisciplinary holistic analysis of biological systems, which coincides with the idea of the holistic view of traditional Chinese medicine. In this review, we summarized the use of network pharmacology technology through studying Chinese medicine single medicine or Chinese medicine compound research ideas and methods for the treatment of ulcerative colitis, based on the application of the current network pharmacology in Chinese medicine research, including the important role in the mechanism of the prediction and verification, to search for new ideas of disease diagnosis and treatment, this paper summarizes the application of network pharmacology in the treatment of ulcerative colitis in traditional Chinese medicine, including monotherapy and compound therapy, and considers that relevant researches have fully demonstrated the function characteristics of multi-component, multi-target, and multi-pathway of traditional Chinese medicine, and can also explain the connotation of "selecting appropriate treatment methods according to the differences and similarities of pathogenesis" of traditional Chinese medicine. Finally, we raise important questions about the prospects and limitations of network pharmacology, such as differences caused by different data collection methods、a considerable lag, and so on.